2005
DOI: 10.1093/toxsci/kfi288
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of CYP1A, 2B, and 3A Genes in the F344 Rat following Exposure to a Polybrominated Diphenyl Ether Mixture or Individual Components

Abstract: Polybrominated diphenyl ethers (PBDEs), used as flame retardants, have been detected in the environment and in mammalian tissues and fluids. Evidence indicates that PBDE mixtures induce CYPs through aryl hydrocarbon receptor (AhR)-dependent and -independent pathways. The present work has investigated the effects of individual components of a commercial PBDE mixture (DE71) on expression of CYP1A1, a biomarker for activation of the AhR (dioxin-like), and CYP2B and CYP3A, biomarkers for activation of the constitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(90 citation statements)
references
References 30 publications
5
82
2
Order By: Relevance
“…Flame retardant products containing lower molecular weight PBDEs have shown the ability to induce CYP1A1 in rodents (von Meyerinck et al 1990;Fowles et al 1994;Zhou et al 2001Zhou et al , 2002; therefore, the possibility of PBDE-mediated dioxin-like toxicity has been of concern. However, we have demonstrated that polybrominated dibenzodioxins and furans detected in PBDE preparations are likely responsible for dioxin-like properties observed in prior studies of these chemicals in rodents (Sanders et al 2005). Conversely, our work showed that BDE47, BDE99, and BDE153 up-regulated CYP2B and CYP3A gene expression in rats within the same order of magnitude as non-dioxin-like PCB153.…”
Section: Introductionmentioning
confidence: 38%
See 1 more Smart Citation
“…Flame retardant products containing lower molecular weight PBDEs have shown the ability to induce CYP1A1 in rodents (von Meyerinck et al 1990;Fowles et al 1994;Zhou et al 2001Zhou et al , 2002; therefore, the possibility of PBDE-mediated dioxin-like toxicity has been of concern. However, we have demonstrated that polybrominated dibenzodioxins and furans detected in PBDE preparations are likely responsible for dioxin-like properties observed in prior studies of these chemicals in rodents (Sanders et al 2005). Conversely, our work showed that BDE47, BDE99, and BDE153 up-regulated CYP2B and CYP3A gene expression in rats within the same order of magnitude as non-dioxin-like PCB153.…”
Section: Introductionmentioning
confidence: 38%
“…Tetra-, penta-, and hexaBDEs, major congeners detected in mammalian tissues and fluids, are components of commercial flame retardant products such as Great Lakes DE-71™ (DE71) and Bromkal 70-5DE™ (BK70) (Sjödin et al 1998;de Wit 2002;Chen et al 2006a). The DE71 used in previous studies in our laboratory contained (by peak area as determined by GC/MS) 36% 2,2′,4,4′-tetraBDE (BDE47), 42% 2,2′,4,4′,5-pentaBDE (BDE99), and 3% 2,2′,4,4′,5,5′-hexaBDE (BDE153) (Sanders et al 2005); similar to respective amounts of the three congeners (37, 35, and 4%) in BK70 (Sjödin et al 1998). These, as well as 2,2′,4,4′,6-pentaBDE (BDE100) and 2,2′,4,4′,5,6′-hexaBDE (BDE154), are the major congeners in both BK70 and DE71 (Sjödin et al 1998;Chen et al 2006a), and are the prevalent congeners detected in human tissue and fluid samples (Hites 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Various PBDEs have been reported to induce mixed-type monoxygenase in vivo. For example, DE-71 was reported to induce CYP1A1 and CYP2B in rats (Zhou et al 2001), while BDE-47, −99, and −153 upregulate CYP2B and CYP3A, also in rat (Sanders et al 2005). In a recent study in mice, BDE-47, −99, and −209 were found to induce expression of CYP3A11 and CYP2B10 by activating the pregnane X receptor (PXR) (Pacyniak et al 2007).…”
Section: Toxicity Of Pbdesmentioning
confidence: 99%
“…For example, technical PBDE mixtures have been shown to induce both phase I and phase II xenobiotic metabolising enzymes in in vitro and in vivo experiments (Siddiqi et al, 2003) and may thus have adverse effects comparable to TCDD and dioxin-like PCBs on hepatic vitamin A homoeostasis. However, Sanders et al (2005) reported only a weak up-regulation of CYP1A1 (a biomarker for activation of the AhR) by DE-71, a PBDE technical mixture, and BDE-47, -99 and -100 in rats exposed to high concentrations. On the contrary, PBDEs appeared to be more able to up-regulate CYP2B and CYP3A, both biomarkers for activation of Constitutive Androstane and Pregnane X Receptors (CAR and PXR, respectively).…”
Section: Relationships Between Pbdes Meo-pbdes and Vitamin Amentioning
confidence: 99%
“…On the contrary, PBDEs appeared to be more able to up-regulate CYP2B and CYP3A, both biomarkers for activation of Constitutive Androstane and Pregnane X Receptors (CAR and PXR, respectively). Sanders et al (2005) suggested thus that PBDEs more likely mediate their toxicity through AhR-independent mechanisms. It has been shown recently that CYP3A was involved in the hepatic metabolism of retinoic acid (Ross and Zolfaghari, 2011), suggesting that PBDEs may affect vitamin A metabolism, in part, through this pathway.…”
Section: Relationships Between Pbdes Meo-pbdes and Vitamin Amentioning
confidence: 99%